Pengaruh Kepemilikan Institusional, Kepemilikan Manajerial dan Leverage terhadap Nilai Perusahaan pada Perusahaan Properti yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2021 - Eni, Cahya; Rakhmanita, Ani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Indonesia IMF predicts that the economy will grow by 5% in 2023, and this prediction is supported by the high demand for housing and the prospects for the property sector in Indonesia which continues to grow. A company's primary objective is to raise its value, which is represented in the market price of its shares. This study seeks to ascertain the impact of managerial ownership, institutional ownership, and leverage (DER) on price to book value in real estate companies listed on the IDX. Research of this kind is quantitative. The information used in this study is secondary information. Purposive sampling with a variety of linear regression analysis approaches was the sampling strategy employed in this investigation. According to data analysis findings, management ownership and partially institutional ownership have a positive and significant impact on price to book value, however leverage as measured by the Debt to Equity Ratio (DER) has no impact. Institutional ownership, management ownership, and leverage, as measured by the Debt to Equity Ratio (DER), all have an impact on price to book value simultaneously. Keywords: Institutional Ownership, Managerial Ownership and Leverage